HUBUNGAN KUANTITATIF STRUKTUR-AKTIVITAS TURUNAN 2- FENILPIRIMIDIN-4-AMIN SEBAGAI SENYAWA ANTIKANKER - Fauzi Nugraha, Ahmad
Cancer is one of common causes leading to death worldwide. In 2012, lung cancer was responsible for 30% of death from overall cancer. 2-Phenylpyrimidin-4-amine has anticancer activity by catalyzing the removal of ubiquitin from modified proteins, whereas dysfunction in ubiquitin-dependent signaling pathways has been linked to various human diseases, especially cancer. The research was aimed to determine the best Quantitative Structure-Activity Relationship (QSAR) equation, in order to obtain new derivatives with higher inhibition activity than that of the parent compound in non-small cell lung cancer cells (NSCLC). Modeling and optimization of the geometry structure were done by Gaussian. Calculation of predictor’s value and multilinear statistical analysis were performed by MOE 2009.10 and SPSS Statistics 16.0, respectively, and the results were validated by Leave One Out method. The designs of new derivatives were made according to the Topliss scheme. The new derivates with the higher inhibition activity were docked to the monoubiquitinated Proliferating Cell Nuclear Antigen (Ub-PCNA) to observe their affinity based on energy value using Autodock 4.2.5.1. The best QSAR equation of 2-phenylpyrimidin-4-amine derivatives is log IC50 (µM) = 0.135(±0.330) ? 0.014(±8.213x10 ?3 ) x (AM1_HF) ?2.071(±1.125) x (AM1_LUMO) ?3.731(±0.090) x (log P) ?2.578(±0.056) x (log S). The QSAR equation which is influenced by the heat formation, Lowest Unoccupied Molecular Orbital (LUMO) energy, logarithm of lipophilicity (partition coefficient), and logarithm of the solubility was used to design 24 new derivatives. It has been found that 24 new compounds have IC50 lower than that of the parent compound. Two of them have been proven having higher affinity to the Ub-PCNA receptor due to its number of hydrogen bond, amino acid residue, binding energy, and inhibition constant.